2019
DOI: 10.1039/c9ra01469a
|View full text |Cite
|
Sign up to set email alerts
|

Reducing leakage current and dielectric losses of electroactive polymers through electro-annealing for high-voltage actuation

Abstract: The electro-annealed polymer, the E-TH sample, shows a reduction in leakage current of 80% for very high electric fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…As reported in literature 19,20 and in our previous works 10,13 , terpolymer P(VDF-TrFE-CFE) commonly exhibits a purely electrostrictive behavior. Indeed, the mechanical strain response shows a quadric dependence with the applied electric field, and as a result, its direction is not dependent on the polarity of the voltage excitation.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…As reported in literature 19,20 and in our previous works 10,13 , terpolymer P(VDF-TrFE-CFE) commonly exhibits a purely electrostrictive behavior. Indeed, the mechanical strain response shows a quadric dependence with the applied electric field, and as a result, its direction is not dependent on the polarity of the voltage excitation.…”
Section: Methodssupporting
confidence: 66%
“…Subsequently, casted films are heated up at 70 °C for 1 h to ensure complete solvent removal. Films are then peeled off and placed on polytetrafluoroethylene (PTFE) foils, and thermal annealing at 102 °C is performed to promote crystallinity 13 . The annealing temperature was chosen as the onset of the melting peak for the second melting of terpolymer powder that was determined via DSC.…”
Section: Methodsmentioning
confidence: 99%
“…Ideal dielectrics are assumed to be perfect insulators 36 (that is, they present infinite resistivity). However, in reality, their resistivity is finite, leading to a passage of current when subjected to applied voltages commonly known as current leakage 36,37 . This leakage is often undesirable, as it decreases the effective electric field needed for the functioning of multiple devices and promotes material degradation processes [37][38][39] .…”
Section: Electric Field Leakage Through Dielectric Materialsmentioning
confidence: 99%
“…However, in reality, their resistivity is finite, leading to a passage of current when subjected to applied voltages commonly known as current leakage 36,37 . This leakage is often undesirable, as it decreases the effective electric field needed for the functioning of multiple devices and promotes material degradation processes [37][38][39] . In materials often used in nanopores, such as SiO2, Si3N4 and Al2O3, this leakage is often associated with Poole-Frenkel effects 36,40 and it manifests at voltages of the order of 10 8 V/m 41 .…”
Section: Electric Field Leakage Through Dielectric Materialsmentioning
confidence: 99%
“…We observed that the current behavior of the plasticized terpolymer at a applied high electric field ( E ≥ 10V μm −1 ) is unconventional with respect to pure terpolymer and other electrostrictive polymers . According to empirical modeling, an estimated permittivity from Equation using experimental current allows to evaluate the electromechanical response of the plasticized terpolymer at a high applied voltage.…”
mentioning
confidence: 99%